In the Wave of Changes... Baroque Influences and Serbian Literature in the 18th Century - Lis-Wielgosz, Izabela (Poznańskie Studia Slawistyczne, 2024)
This article is a review of Justyna Romanowska’s study entitled The Polish-UkrainianRussian Contexts of Metaphysical Poetry of Serbian Baroque (published by Scriptum, Kraków, 2022). This book focuses on the influences of Polish-Ukrainian-Russian poetical strategies, contexts and patterns on Serbian metaphysical poetry in the 18th century . Justyna Romanowska’s study is a part of the discussion on the developmental process of Serbian literature, as well as the long debate on the existence of the Baroque era in Serbian literature.